Back to Nature: Sebuah Tinjauan Filosofis tentang Konsep Pendidikan Rousseau - Tabrani ZA (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Rousseau's fundamental views or assumptions which discuss anthropology and epistemology lead to how children learn. These assumptions on human nature are related to the rapid development of human civilization, especially in this modern era. The purpose of human life which was originally good is reduced only by various developments of civilization so that humans increasingly leave their integrity as humans who are free, autonomous, and of good nature. This fact made Rousseau aware that the culture which had been admired and proud of by many people in Europe was in fact not the pinnacle of human life but a reflection of the decay of civilization. Culture, art, and science, along with technology, seem to have destroyed humanity and have created unhealthy dependence and injustice. One of the philosophers who criticized the situation of human civilization and proposed a revolutionary educational system in the early modern era was Jean Jacques Rousseau. Emile is one of Rousseau's most revolutionary works on education. In his book, Emile, Rousseau puts his thoughts on education back to nature in the book. Rousseau's view of education is broken down by age group and emphasizes a return to nature. Emile, as the main character, grows up in accordance with natural conditions and learns by the Rousseau method which emphasizes learning according to development and natural inquiry processes. It aims to achieve fundamental changes in education to free the individual from the shackles of civilization. Civilization is not only detrimental to society; it also harms the individual. Education should encourage children's self-expression and development.